A Didactic Approach to Kinetic Parameter Estimation: a Case Study of Glycerol Carbonate Synthesis from Glycerol and Dimethyl Carbonate - Juan Carlos Ojeda-Toro; Javier A. Mancera-Apolinar; Jaime Eduardo Arturo Calvache (Chemical Engineering Transactions)
This study introduces a didactic methodology for estimating kinetic parameters, it was designed as a practical guide for chemical engineering students, focusing on the synthesis of glycerol carbonate (GC) from glycerol (G) and dimethyl carbonate (DMC) as a case study. Notably, the kinetics of this reaction had not been previously adjusted in the literature, offering a novel opportunity to explore and model its behavior. Experimental datasets from two distinct cases, using CaO and carbide slag as heterogeneous catalysts under different reaction conditions were analyzed. Both elementary and non-elementary rate laws were applied within a pseudo-homogeneous model framework, with kinetic parameters determined by minimizing the discrepancy between experimental and calculated glycerol conversion values using MATLAB®. Results demonstrate that non-elementary rate laws provide a superior fit to experimental data (average relative deviation-ARD: Case 1-1.26% and Case 2-2.33%) compared to elementary rate laws (ARD: Case 1-2.75% and Case 2-6.06%), underscoring the importance of accounting for reaction complexities in kinetic modelling. This methodology serves as a step-by-step educational tool, enhancing students’ understanding of parameter estimation, model validation, and reaction optimization while showcasing the integration of theoretical and computational tools in addressing real chemical engineering issues.